Organizations coupled with communities: the strategic effects on firms engaged in community-coupled open innovation. (14th October 2016) - Sims, Jonathan; Seidel, Victor P.
Abstract: The study of open innovation has primarily focused on the benefits and consequences of inbound or outbound innovation exchange between firms; however, increasingly firms may be engaged in simultaneous inbound and outbound exchange forming a "coupled" approach. Furthermore, firms increasingly collaborate with communities as sources of innovation, but how does such "community-coupled open innovation" affect a firm? Through an in-depth study of 250 firms collaborating with a leading open source software community, we show how this approach incorporates not only the exchange of intellectual property but also the provision of help. We find that while community-coupled open innovation does not affect productivity, it can expand a firm's social ties, lead to a more conservative strategic posture, and shift its innovation focus. Implications for our theories of open innovation in the context of communities are discussed.